Study of HAZOPs in the Screening Unit of the Industrial Gas Wastewater Treatment Plant - Nora Amalia Novitrie; Mey Rohma Dhani; Aulia Nadia Rachmat; Yessica Novrita Devi (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
The filtration is the final stage of industrial gas wastewater treatment for clean water generation. Filtration is an operation of separating solid and liquid materials by filter medium. In filtration process the driving force such as pressure difference by gravitation or rotary power cause the feed to flow. The process parameters in the filtration process need to be monitored and controlled because deviation or abnormality of the process parameters will cause operating failures. This condition requires a more in-depth identification so that the risks of operating failures can be minimized. HAZOPs is a method to identify hazard that caused by deviation of parameters using guide words. Steps of the research consisted of early survey, literature study, and filling the HAZOPs worksheet such as determine study node, deviation, parameter, guideword, risk evaluation, and risk control. The results of the study show that there were four potential deviations from three parameters which were flow, pressure, and temperature. Risk values analysed were medium and low. Recommendation of the system are adding alarm, valve, changing filter regularly, and scheduling the routine maintenance.